When there is more than one motive: a study on self-reported hate crime victimization among Swedish university students - Andersson, Mika (International review of victimology, 2018)
The present study examines experiences of hate crimes with multiple motives with a focus on policy and theory-related issues. The authors found that every fifth hate crime victim reports having experiences of multiple motives. These victims are more likely to report their victimization to the police in comparison to victims of hate crimes with single motives. The results also show that belonging to several socially vulnerable groups does not correlate with higher levels of repeat victimization. This is in contrast with intersectional theory as it would predict heightened levels of victimization among such individuals. Lastly, the results show that individuals who belong to more than one socially vulnerable group are more likely to experience hate crimes with multiple motives. Implications for policy and intersectional theory are discussed.